LINGUAL PHRENECTOMY WITH THE USE OF IODINE LASER IN INFANT PATIENT: CASE REPORT - Carolina Reis De Paiva, Ana; Farias Valente, Yasmin; de Fátima Souza Araújo, Andréia; Maria Mendes Ribeiro, Suelly (Health and Society, 2023)
Objective: to approach the surgical process better known as frenectomy to solve Ankyloglossia, a condition that restricts the movement of the tongue. This change is characterized as congenital, consisting of fibrous connective tissue, which affects the tip of the tongue to the floor of the mouth. Case report: A 3-year-old female patient attended the Children’s Dental Clinic at the University Center of the State of Pará, presenting the Linguinha Test report proving the ankyloglossia. In the preoperative period, Ibuprofen 50mg / ml was prescribed, 18 drops 1 hour before the surgical procedure and 6/6 hours after surgery for 2 days. However, surgery was performed for the better development of the patient using high intensity iodine laser therapy ((2300mW-0: 00-continuous Surgery-DMC), successfully finishing the procedure. After 24h and 48h, the laser was applied low intensity (66 NM, 100 mW, 2J-DMC) to enhance the benefit of iodine laser. Conclusion: The present case indicates the use of the laser as a safe and effective technique for performing lingual frenectomy in a child patient.